1988
DOI: 10.1038/bjc.1988.28
|View full text |Cite
|
Sign up to set email alerts
|

Ha-ras restriction fragment length polymorphisms in colorectal cancer

Abstract: Summary The possibility of an association between restriction fragment length polymorphisms (RFLPs) at the Ha-ras gene locus and susceptibility to develop colorectal cancer has been investigated. Leucocyte DNA from 46 carcinoma patients and 49 controls was analysed by Southern blotting to determine the size distribution of restriction fragments containing the variable tandem repeat 3' to the Ha-ras gene. Four predominant allelic fragments were found in both groups (in AvalI digests having sizes of 1.55, 2.0, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…On the other hand, the overall prevalence of rare alleles was not significantly different between cancer and control groups in studies of colorectal cancer [19], hepatocellular carcinoma [18], melanoma [21], urothelial [22] and NSCLC [7]. Our analysis of c-Ha-ras polymorphism in NSCLC patients also failed to confirm the hypothesis that rare alleles represent a major risk factor for common types of cancer.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…On the other hand, the overall prevalence of rare alleles was not significantly different between cancer and control groups in studies of colorectal cancer [19], hepatocellular carcinoma [18], melanoma [21], urothelial [22] and NSCLC [7]. Our analysis of c-Ha-ras polymorphism in NSCLC patients also failed to confirm the hypothesis that rare alleles represent a major risk factor for common types of cancer.…”
Section: Discussioncontrasting
confidence: 48%
“…Increased numbers of this allele in the group of patients with NSCLC has been observed [7]. Several studies have reported a relative increase in frequency of a3-and a4-alleles in different cancer groups [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The best documented example concerns the Ha-ras locus where rare alleles, detected by cleavage of DNA with MspI/HpaII, are found more frequently in patients with various cancer types than in healthy controls (Krontiris et al, 1985;Lidereau et al, 1986; Hayward et al, 1988a). However, other workers have found no such association between particular Ha-ras alleles and cancer (Thein et al, 1986;Gerhard et al, 1987;Ishikawa et al, 1987;Wyllie et al, 1988).Recently, a TaqI RFLP at the same human proto-oncogene locus was reported to be present at a higher frequency in human malignant melanoma (Radice et al, 1987;Hayward et al, 1989).Other RFLPs specific for a number of different gene loci have been associated with increased risks of various human cancers: TaqI RFLP of the TGFa gene in cutaneous malignant melanoma (Hayward et al, 19886) and EcoRI RFLP of the c-mos locus in breast cancer (Lidereau et al, 1985), intracranial cancer (Diedrich et al, 1988), human myeloid leukemia (Revoltella et al, 1985) and esophageal cancer (Hollstein et al, 1986), in contrast with the results of Chenevix-Trench et al (1989) in non-Hodgkin's lymphoma patients.EcoRI-restricted human DNAs show fragment length polymorphism of L-myc defined by 2 alleles: 10.0-kb and 6.6-kb fragments (Nau et al, 1985;Bieche et al, 1990). The presence of the S fragment (6.6-kb) is associated with susceptibility to local metastasis in lung cancer (Kdwashima eta/., 1988), distal metastasis in renal cancer (Kakehi and Yoshida, 1989) and osteosarcomas in male patients .…”
mentioning
confidence: 95%
“…Studies have indicated that rare HRAS1 alleles may be of value in lung cancer risk assessment [44,45]. Rare HRAS1 alleles also represented an inherited factor which predisposed the development of colorectal cancer [46,47]. Rare HRAS1 alleles may function as a modifier of ovarian cancer risk in both sporadic and hereditary ovarian cancer [48].…”
Section: Discussionmentioning
confidence: 99%